The hemostatic profile of cold-stored whole blood from non-greyhound and greyhound dogs over 42 days - Cooper, James L.; Sharp, Claire R.; Boyd, Corrin J.; Claus, Melissa A.; Rossi, Gabriel (Frontiers in Veterinary Science, 2023)
Objectives: To compare hemostatic characteristics of cold-stored whole blood (CSWB) from non-greyhound (NGD) and greyhound dogs (GD) over 42 days of storage, notably, platelet closure time (PCT) (NGD only), manual platelet count (PLT) (GD only), ellagic acid (INTEM) and tissue factor activated (EXTEM) rotational thromboelastometry, prothrombin (PT) and activated partial thromboplastin time (aPTT), fibrinogen concentration (FIB), and activities of factors (F) FII, FV, FVII, FVIII, FIX, FX, FXIII antigen (FXIII:Ag) and von Willebrand factor antigen (vWF:Ag). Design: Whole blood from 10 NGD and 10 GD, was refrigerated in CPD blood bags at 4°C for 42 days. Blood was analyzed before refrigeration (day 0) and at day 1 (d1), 3, 5, 7, 10, 14, 17, 21, 24, 28, 31, 35, 38 and 42. Multivariate linear mixed effects models were created to evaluate coagulation parameters over time and compare NGD and GD. Significance was set at P <0.05. Results: The PCT for all NGD CSWB was above the device limit by d7. The PLT for GD CSWB did not change during storage. The mean alpha-angle for INTEM and EXTEM reached 50% of baseline at d38 and d31 for NGD, and d31 and d17 for GD CSWB. The mean MCF for INTEM and EXTEM reached 50% of baseline at d42 and d28 for both GD and NGD. PT and aPTT for NGD and GD increased over time. For NGD CSWB, FVIII and vWF:Ag activities reached 50% of baseline at d7 and d28 respectively, and FIB reached 0.982 g/dL by d24. For GD CSWB, FVIII, FXIII:Ag and FV activities reached 50% of baseline by d3, d38, and d38 respectively, and FIB was 0.982 g/dL at baseline. Alpha-angle and MCF for both INTEM and EXTEM, and activities for FII, FV, FIX, FXIII:Ag were significantly lower, and vWF:Ag was significantly higher overall in GD CSWB compared with NGD. Conclusions: The in vitro viscoelastic parameters of GD and NGD CSWB declines over 42 days, but numerous hemostatic parameters remain within 50% of baseline for more than 14 days. CSWB from GD compared to NGD has reduced hemostatic activity overall, but a similar pattern of decline.